Competitividad Internacional del Aceite de palma colombiano 2000-2020 (2020)
The main objective of this research work is focused on describing and analyzing in depth in the contexts of international trade, as has been the current situation of the Colombian palm sector in the course of the years (2000-2020) and how it has contributed to the competitiveness of Colombia in the international market. The Colombian palm growing sector has taken on great importance within the agro industrial activities, since it has shown that the consumption of healthy foods has been superior to the derivatives that exist of olive, vegetable and animal oils; It is good to recognize this, since Colombia is the first country to produce palm oil, and that it has more than 350,000 hectares, as well as its climatic conditions have allowed the cultivation of such a product. It is noteworthy that the export of palm oil has had a much higher growth, since in 2016, according to figures from the National Administrative Department of Statistics (DANE), it had a growth of 42% and a participation of 9% within of the Agricultural Gross Domestic Product and 8% in the agricultural benchmark, which is beneficial for several farmers. This research work has been developed according to a series of data analysis, and therefore, this research is quantitative, which, its main sources of information are the National Administrative Department of Statistics, different government entities and agencies officers.